The influence of different training conditions on the kinematics of long jump-specific exercise in young female jumpers - Makaruk, H.; Mastalerz, A.; Starzak, M.; Buszta, M. (Polish Journal of Sport and Tourism, 2015)
This study examined the changes in the kinematic parameters of long jump-specific technical exercise performed in different training conditions. Material and methods. The study involved a group of young female athletes who volunteered to participate in the research. The key variables for long jump performance were measured using the Xsens MVN system. A three-way ANOVA (general linear model with repeated measures; factors: surface x hurdle x number of jumps) was used to determine if significant differences existed between the testing conditions. Results. The main finding of this study was that the tartan surface resulted in significantly (p < 0.05) greater velocities of the centre of mass of the body (CM) or parts of the athlete`s body than the grass surface. The second important finding was that the hurdles condition provided significantly (p < 0.05) greater velocity of the CM when landing and shorter contact time compared to the condition without hurdles. Conclusions. The findings of the study indicate that technical exercise should be performed on harder surfaces such as a tartan track rather than softer ones (e.g. grass) due to more beneficial movement characteristics and greater potential for the automaticity of movement during specific training tasks.